Existence of Positive Solutions for a Class of Variable Exponent Elliptic Systems - Ala, S.; Afrouzi, G. A. (MATHEMATICA SCANDINAVICA, 2016)
We consider the system of differential equations \[ \begin{cases} -\Delta_{p(x)}u=\lambda^{p(x)}f(u,v)&\text{in $\Omega$,}\\ -\Delta_{q(x)}v=\mu^{q(x)}g(u,v)&\text{in $\Omega$,}\\ u=v=0&\text{on $\partial\Omega$,}\end{cases} \] where $\Omega \subset\mathsf{R}^{N}$ is a bounded domain with $C^{2}$ boundary $\partial \Omega,1<p(x),q(x)\in C^{1}(\bar{\Omega})$ are functions. $\Delta_{p(x)}u=\mathop{\rm div} olimits(| abla u|^{p(x)-2} abla u)$ is called $p(x)$-Laplacian. We discuss the existence of a positive solution via sub-super solutions.